PENINGKATAN KEMAMPUAN LITERASI ANAK USIA 4-5 TAHUN MELALUI PENGUNAAN MEDIA WOODEN PUZZLE DI KB BINTANG HARAPAN TAHUN AJARAN 2025-2026 - Ika Fatmawati; Wijaya Adi Putra; Firman Ashadi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to improve the literacy skills of children aged 4–5 years through the use of Wooden Puzzle media at KB Bintang Harapan. The method used was Classroom Action Research (CAR), conducted in two cycles including planning, action, observation, and reflection stages. The participants consisted of 7 children. The results showed a significant improvement in children’s literacy skills. In the pre-cycle stage, none of the children achieved mastery (0%). In Cycle I, literacy mastery increased to 60% (4 children). In Cycle II, all children mastered the literacy indicators (100%). These findings demonstrate that the Wooden Puzzle media effectively enhances children’s interest and provides concrete learning experiences, thus successfully improving early childhood literacy skills.